Pencegahan Penyakit Tbc Paru Yang Utama Dimulai Dari Dalam Rumah Penderita - Sabina Gero; Mariana Sayuna (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Pulmonary TB disease as a tropical disease, was found to increase from 385 cases in 2014, to 600 cases in 2015 in Malaka district, Wehali village, Betun Public Health Center of Malacca District by the amount. This increase in numbers indicates the weak behavior of pulmonary tuberculosis prevention in Malacca society. The aim of the study was to analyze the relationship between preventive behavior and the risk of pulmonary tuberculosis transmission among people at home. Method. The research was conducted by a cross-sectional method, in population, all malaria patients in Wehali village were 30 people. The analysis was performed by univariate and bivariate using chi-square analysis, and observation of the patient at home. Results. The prevention behavior of TBCparu patients in Wehali village of Malaka district is 76.6% enough / less. Patients who transmit lung tuberculosis disease to family members is 66.7% (20 patients). The relationship between prevention behavior and transmission of pulmonary tuberculosis in the home/family was significant with p <0.05 (p = 0.000). The prevalent ratio that shows the behavior of tuberculosis patients has the potential to transmit the disease to households by 2.6 times. Conclusion. Prevention of important tuberculosis disease begins within the patient's own home. Role of Drinking Drugs Important drugs are improved not only to monitor medication but also how to prevent TB transmission to begin within the home of pulmonary tuberculosis patients.